LEKSIKON TATA BOGA ETNIS TIONGHOA TIOCIU DI KABUPATEN KUBU RAYA - Peter Oktavianda Andreas; Agus Syahrani; Mellisa Jupitasari (Universitas Tanjungpura, 2022)
In this study case how was lingual unit form, the meaning, and also the level of understanding language. This study focus to descripe and analized the Lexicon Cullinary Art Etchnicity Tionghoa Tiociu at Kubu Raya Region. The method that been used in this study are Kuantitatif and Kualitatif. Resourses data in this study is form the informan at the place, Data Collection techniques are observation, interview, recording, writing and questioner. The result data been get from this study are 96 Lexicon Cullinary Art Etchicity Tionghoa Tiociu at Kubu Raya Region stand from 18 lexicon of appatizer, 45 lexicon of main course, 14 lexicon of dessert, 11 lexicon of drinks, and 8 lexicon of how to cook. Based on lingual unit form about 77 lexiconof phrase. The meaning lexicon Cullinary Art Ethnicity Tionghoa Tiociu at Kubu Raya Region based on the lexical meaning 96 lexicon and 28 lexicon of cultural.Keywords: Lexicon, Cullinary Art, Etchicity Tionghoa Tiociu